PENDUGAAN POTENSI KEBUN KARET RAKYAT SEBAGAI CADANGAN KARBON DI KECAMATAN CEMPAKA KOTA BANJARBARU PROPINSI KALIMANTAN SELATAN - Tuti Haryati; Idiannor Mahyudin; Abdi Fithria; Abdul Haris (Universitas Lambung Mangkurat, 2014)
Calculation of carbon stocks using allometric equation system is done to get the value of carbon stocks in smallholder rubber plantations in Cempaka district, Banjarbaru City South Kalimantan needs to be done in order to know the carbon stocks contained in the smallholder rubber plantations. Based on the statistical report plantation Banjarbaru City first quarter of 2013, the people's rubber plantation area of 986 hectares. However, data obtained from field surveys note that the data are actually rubber plantation area of 1318.61 ha. This study aims to determine the amount of carbon stocks in jungle rubber at different age levels and determine other factors that affect carbon stocks in jungle rubber. The methods of this study includes data collection and determination of the point of the plot as well as the selection of a plot point. Primary data collection is done by taking the coordinates of the field (the survey) using a GPS (Global Positioning System), and the data analysis was conducted on the data collection for the measurement of carbon stocks above the surface of the carbon on the surface and below the surface measuring carbon stocks. The results showed that the highest carbon stocks contained in the 7-year age group with a score of 716.61 Mg carbon stocks / ha followed by 5-year age group was 685.21 Mg / ha, 3-year age group was 603.51 Mg / ha and the smallest to the carbon value of 585.62 Mg / ha. While based on the factors that influence the obtained results that the pH is tolerated for acid soil types, categorized as very low C Organic, Organic materials in the high category, total N and P were categorized very low, K can be categorized as high. All these factors are still can be considered good for the growth of rubber trees until they reach the age of 30 years. Concluded that the more composition and structure of rubber gardens stands then the greater carbon storage in stands in people rubber plantation area at the Cempaka district Banjarbaru City and soil conditions can be categorized as land that can still be used for the growth of rubber trees.